Language regime change in Peru: authoritarian state traditions and unexpected effects of democratic reforms - (:unkn) unknown (Cambridge University Press, 2024)
Peru is a multiethnic society whose postcolonial language regime was marked by the dominance of Spanish as the exclusive language of state bureaucracy up until recently. There are now forty-eight different Indigenous languages recognized by the state. Th...
Keywords: Política lingüística; Democracia